Analysis of organic functional groups and some trace heavy metals in the settleable dust particles (dustfall) of Sulaimani City/KURDISTAN REGION-IRAQ. - Majid, Salih N. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Ambient settleable (dustfall) dust particles samples were collected during August 2009 to March 2010 from 18 locations in Sulaimani City/KRI for qualitative analyzing by Fourier Transform Infrared (FTIR) spectroscopy instrument to characterize the common functional groups that existed in the samples. Furthermore, the samples were quantitatively analyzed for the heavy metals contents of; V, Co and As by Inductively Coupled Plasma-Optical Emission Spectroscopy ICP-OES. The collected samples involved samples of settleable dust particles from local source of the city (location 1 to 15) and settleable dust particles from dust storm event of 22 February, 2010 (location 16 to18). The FTIR analysis identified the following functional groups; Sulfinate ester; Sulfoxide; Sulfate ion; P. Amine (bend.); Carbonyl; Thiol; Alkanes HC; P. Amine (str.); Bonded and free hydroxyl group in all the samples of (1 to 15) for the local source of dust particles except sample location number 6 which was free from sulfoxide, p. amine (bend.), carbonyl and p. amine (str.) as compared to the samples of other locations and it was also the only sampling location that had a silicate group. Moreover, sample location number 13 was the only location that had an extra functional group of isocyanide or alkynes HC functional group. For the dust storm samples of location numbers 16, 17 and 18 had also all the above mentioned 9 functional groups except the alkanes HC functional group. On the other hand, the concentration ranges of the studied heavy metals were (0.20 – 3.20), (2.02 – 5.45) and (2.89 – 45.50) mg dust kg-1 dust for As, Co and V respectively in all the studied locations.
Keywords: Settleable dustDustfall; Functionalgroups; Dust storm,Heavy metals